Pengaruh Media Perendam Terhadap Permeabilitas Membran Polisulfon - Cynthia L. Radiman; Yuliany Yuliany; Veinardi Suendo (Institut Teknologi Bandung, 2002)
The performance of membrane separation processes can be generally expressed by membrane permeability and permselectivity. One of the important factors affecting membrane permeability in the filtration process of aqueous solution is membrane hydrophilicity. In this experiment, the effects of various soaking mediums, i.e. ethanol, isopropanol and butanol on the permeability of polysulfone membrane were studied. The results showed that soaking in ethanol gave the greatest effect proved by the drastic increase in permeability for membrane before and after soaking, i.e. from 263.57 L/m2.h to 645.49 L/m2.h. On the other hand, the membrane rejection against dextran T-500 before and after soaking in ethanol only showed a slight decrease from 96 % to 95 %. In addition, the contact angle between water and soaked-in-ethanol membrane gave the smallest value, i.e. 19.8Â°. The interaction between alcohol and soaked membrane is then considered as a reversible physical adsorption since the permeability reached its initial value after being soaked again in water for a long period. The experimental data showed that ethanol could enhance the permeability of polysulfone membrane by increasing the membrane hydrophilicity without giving any significant decrease in the membrane permselectivity.